2011
DOI: 10.1016/j.mrfmmm.2010.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone up-regulates PTEN expression and induces apoptosis in doxorubicin-resistant human breast cancer cells

Abstract: The use of innocuous naturally occurring compounds to overcome drug resistance and cancer recalcitrance is now in the forefront of cancer research. Thymoquinone (TQ) is a bioactive constituent of the volatile oil derived from seeds of Nigella sativa Linn. TQ has shown promising anti-carcinogenic and anti-tumor activities through different mechanisms. However, the effect of TQ on cell signaling and survival pathways in resistant cancer cells has not been fully delineated. Here, we report that TQ greatly inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
143
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(151 citation statements)
references
References 46 publications
7
143
1
Order By: Relevance
“…Its purported health benefits include anti-inflammatory, anti-oxidant and anti-hypertensive actions. We have shown that TQ induces apoptosis in HL-60 leukemia cells and MCF-7/DOX doxorubicin-resistant breast cancer cells [22], [23]. Additionally, a number of other studies have reported that the anti-tumor functions of TQ are specific for cancer cells [24], [25].…”
Section: Introductionmentioning
confidence: 67%
“…Its purported health benefits include anti-inflammatory, anti-oxidant and anti-hypertensive actions. We have shown that TQ induces apoptosis in HL-60 leukemia cells and MCF-7/DOX doxorubicin-resistant breast cancer cells [22], [23]. Additionally, a number of other studies have reported that the anti-tumor functions of TQ are specific for cancer cells [24], [25].…”
Section: Introductionmentioning
confidence: 67%
“…Unfortunately, many breast tumor cells are inherently resistant to doxorubicin or can acquire chemoresistance shortly after therapy, which inevitably leads to treatment failure and relapse of the disease (2,3). An accumulating body of evidence suggests that constitutive activation of the NFB pathway can contribute to cancer development, progression, and resistance to cancer therapy (4,5), whereas activation of this pathway by doxorubicin can also render tumor cells more resistant to chemotherapy (6).…”
Section: Discussionmentioning
confidence: 99%
“…Doxorubicin, an anthracycline antibiotic, is one of the commonly prescribed chemotherapeutic agents against a wide-spectrum of cancers including breast cancer (2). However, the clinical efficacy and usefulness of doxorubicin-based treatment regimens is still limited because of dose-limiting toxicity and induction of drug resistance (3). Therefore, there is an urgent need to develop new sensitizing agents that enhance the efficacy of doxorubicin and circumvent chemoresistance.…”
mentioning
confidence: 99%
“…Citrus fruit polysaccharides in vitro inhibiting angiogenesis and cell migration [113] Nutrients 2017, 9, 728 [141] jamun fruit NA in vitro inhibiting proliferation and inducing apoptosis [142] cranberry NA in vitro inducing apoptosis and G1 phase arrest [143] Nutrients 2017, 9, 728 [189][190][191] in vitro -inducing cell cycle arrest -lowering the invasive and metastatic potential -stimulating the expression and secretion of IFNγ [192][193][194][195][196][197] red beetroot betanin in vitro showing a dose-dependent cytotoxic effect [198] Nutrients 2017, 9, 728 inhibiting invasion by reducing MMP-9 expression via blockade of NF-κB activation [204] inhibiting invasion by suppressing invadopodium formation and MMP activity [205] inhibiting growth and sustainability of spheroid generated from adherent breast cancer cells [206] ginger 6-dehydrogingerdione in vitro inducing apoptosis and cell cycle arrest in G 2 /M phase [207] garlic diallyl disulfide in vitro inducing apoptosis though: -inhibition of histone deacetylation -inhibition of ERK and the activation of the SAPK/JNK and p38 pathways [216,217] in vitro and in vivo inhibit proliferation and metastasis via: -suppression of the SRC/Ras/ERK pathway -inactivation of the β-catenin signaling pathway [218,219] garlic diallyl trisulfide in vitro and in vivo inducing apoptosis though: -overproduction of ROS and subsequent activation of JNK and AP-1 -upregulating FAS, Bax and p53, and down-regulating Akt and Bcl-2 [220,221] in vitro -inhibiting migration and invasion; -inhibiting ER-α -decreasing protein level of FoxQ1 [213,222,223] garlic S-allyl mercaptocysteine in vitro inducing mitochondrial apoptosis and cell cycle arrest [214] garlic allicin in vitro inhibiting invasion and metastasis [215] black cumin extracts in vitro inducing apoptosis and inhibiting metastasis [224,225] black cumin thymoquinone in vitro and in vivo inducing apoptosis through: -inhibiting Akt phosphorylation -inducing p38 phosphorylation via ROS generation …”
Section: Synergistic Effects Of Dietary Natural Products With Anticanmentioning
confidence: 99%